Ateizm jako źródło niepokojów ludzkich - Drożdż, Alojzy (Śląskie Studia Historyczno-Teologiczne, 2011)
In the presented article, Author draws attention to the main types of atheism these days. He assumes that at the root of all kinds of atheism lies “anthropological error”. Taking personal anthropology, he claims that without it, the meaningful dialogue with current atheism, is impossible. He draws on teaching of The Second Vatican Council and on the message that: “without God remain only ruins of human morality”. In the second part of publication, Author expands main assumption of prevalent “playful atheism” (ironic). It is widely promoted especially by significant part of the media and all of today’s anthropological ideologies. In the third part Author shows different kinds of alienation of today’s human. These alienation have their source in “anthropological error” and finally in ethical permissiveness.